A comparison of the home‐care and healthcare service use and costs of older Australians randomised to receive a restorative or a conventional home‐care service. (20th January 2014) - Lewin, Gill; Allan, Janine; Patterson, Candice; Knuiman, Matthew; Boldy, Duncan; Hendrie, Delia
Abstract Restorative home‐care services, or re‐ablement home‐care services as they are now known in the UK, aim to assist older individuals who are experiencing difficulties in everyday living to optimise their functioning and reduce their need for ongoing home care. Until recently, the effectiveness of restorative home‐care services had only been investigated in terms of singular outcomes such as length of home‐care episode, admission to hospital and quality of life. This paper reports on a more complex and perhaps more significant measure – the use and cost of the home‐care and healthcare services received over the 2‐year period following service commencement. Seven hundred and fifty older individuals referred for government‐funded home care were randomly assigned to a restorative or standard service between June 2005 and August 2007. Health and aged care service data were sourced and linked via the Western Australian Data Linkage System. Restorative clients used fewer home‐care hours (mean [SD], 117.3 [129.4] vs. 191.2 [230.4]), had lower total home‐care costs (AU$5570 vs. AU$8541) and were less likely to be approved for a higher level of aged care (N [%], 171 [55.2] vs. 249 [63.0]) during follow‐up. They were also less likely to have presented at an emergency department (OR = 0.69, 95% CI = 0.50–0.94) or have had an unplanned hospital admission [OR (95% CI), 0.69 (0.50–0.95)]. Additionally, the aggregated health and home‐care costs of the restorative clients were lower by a factor of 0.83 (95% CI 0.72–0.96) over the 2‐year follow‐up (AU$19, 090 vs. AU$23, 428). These results indicate that at a time when Australia is facing the challenges of population ageing and an expected increase in demand for health and aged care services, the provision of a restorative service when an older person is referred for home care is potentially a more cost‐effective option than providing conventional home care.